Multisensory perception is not influenced by previous concussion history in retired rugby union players - Cunningham, J.; O`Dowd, A.; Broglio, S. P.; Newell, F. N.; Kelly, Á.; Joyce, O.; Januszewski, J.; Wilson, F. (Brain Injury, 2022)
Background: To assess whether concussion history adversely affects multisensory integration, we compared susceptibility to the Sound-Induced Flash Illusion (SIFI) in retired professional rugby players compared to controls. Methods: Retired professional rugby players ((N = 58) and retired international rowers (N = 26) completed a self-report concussion history questionnaire and the SIFI task. Susceptibility to the SIFI (i.e., perceiving two flashes in response to one flash paired with two beeps) was assessed at three stimulus onset asynchronies (70 ms, 150 ms or 230 ms).Logistic mixed-effects regression modeling was implemented to evaluate how athlete grouping, previous concussion history and total number of years playing sport, impacted the susceptibility to the SIFI task. The statistical significance of a fixed effect of interest was determined by a likelihood ratio test. Results: Former rugby players had significantly more self-reported concussions than the rower group (p < 0.001). There was no impact of athlete grouping (i.e., retired professional rugby players and retired international rowers), years participation in elite sport or concussion history on performance in the SIFI. Conclusion: A career in professional rugby, concussion history or number of years participating in professional rugby was not found to be predictive of performance on the SIFI task.